Factors that affect the mechanical properties of kenaf fiber reinforced polymer: A review - Siregar, J. P.; Farah Ayuni, Fauzi; Tezara, C.; Lim, H.Y.; M.H., Yazdi; Moey, L.K.; Lim, J.W. (Faculty Mechanical Engineering, UMP, 2016)
Kenaf fibre has emerged as an important plant cultivated in Malaysia and has been regarded as an industrial crop. The utilization of natural fibres, such as kenaf fibre, in the polymer matrix composites has, in fact, received much attention due to certain attributes, such as low in cost and density, as well as its biodegradability feature. Moreover, numerous potential applications using the kenaf fibre can be explored due to its vast physical and mechanical properties. For instance, chemical treatment, fibre content and form, interfacial adhesion, and water absorption are some of the factors that affect the mechanical properties of kenaf fibre reinforced polymer. Besides, the study on the mechanical properties of kenaf fibre composites is indeed important as it plays an important role in determining a suitable application for various industrial products. In this review work, the factors that affect the mechanical properties of kenaf fibre reinforced polymer composite are highlighted to provide a source of literature for further researches concerning the use of kenaf fibre polymer composites on various applications.